Modus Operandi Kejahatan Skimming Terhadap Nasabah Berdasarkan Perspektif Hukum Perbankan - Asy Syafa, Adia Surya; Santoso, Imam Budi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Behind these new developments, there are different legitimate issues associated with information infringement and electronic trades in banks which, while perhaps not fittingly expected, will unquestionably hurt the bank, general society and clients. The bad behavior of taking client cash by skimming method is one of the advanced infringement (Computerized Bad behavior). In view of the skimming framework, the development is unjustly duplicating the information contained in the alluring stripe contained on Mastercards or ATM/charge cards. This suggests, it will in general be contemplated that skimming is a development associated with the offender's undertaking to unlawfully take data from the ATM/really look at card alluring tape to have control over the loss' record. This study intends to get information about monetary infringement that usage the skimming methodology and about real security for clients who are overcomers of skimming bad behavior. The investigation procedure is juridical regularizing, specifically getting and uniting and inspecting data gained from books, articles and journals and related guideline. The results procured are that bad behavior skimming is an old strategy for client cash robbery which is done by taking client data at the client's ATM with skimmer methods. Legal protection from clients who are harmed on account of the bad behavior of skimming should be possible by criminal means, specifically paying all due respects to the police and the police's commitment to catch the guilty parties. Authentic confirmation through normal guideline by means of the bank overriding the client's money resulting to making sense of the trade against the client's record.